Production and Income Analysis of Salak Sugar Farming in District Pinrang Regency - Sahlan, Sahlan; Wardah, Siti; Aisha, Suci Nur (Indonesian Journal of Advanced Research, 2025)
This study aims to determine the factors that influence the farming of sugar snake fruit (Zalacca Var. Amboinensis) and income of sugar snake fruit (Zalacca Var. Amboinensis) in Katomporang Village, Duampanua District, Pinrang Regency. The types of data collected are primary data and secondary data. The results showed that the production factors that influenced the salak sugar farming in Katomporang Village, the real effect of land area was tcount (2.955) < t0.05, meaning that the larger the land area, the higher the production yield. The real influence of labor was tcount ( -1.272) > t0.05, meaning that if the number of workers increases, it will also affect production results. The real effect of seedlings is tcount (-1.746) > t0.05, meaning that the more expensive the price of seeds, the less ability of farmers to meet the needs of salak seeds. and the real effect of fertilizer tcount (-0.070) > t0.05 means that the more expensive the price of fertilizer, the less ability of farmers to meet the needs of their zalacca seeds, so that salak production will decrease. What has a real effect on the production of salak farming is the land area of ​​1.3862 (X1). Revenue from the production of sugar salak farming is Rp. 11,709,673/0.0032. So the average salak farming income earned by farmers is Rp. 10,530,304/0.0032, this has a great opportunity in the development of salak farming.